Similarity solutions for imploding shocks in non-ideal magnetogasdynamics - Singh L.P.; Singh M.; Husain A. (My University, 2025)
In the present article, similarity solutions of second kind to a problem of imploding cylindrical shock wave in non-ideal magnetogasdynamics are investigated. The equation of state of the medium is assumed to be in the form of the Mie-Gruneisen type. A numerical study of singular points of the differential equations leads to determination of the similarity exponent. Numerical description of the flow field has been presented in non-ideal magnetogasdynamics. The results obtained are compared with the numerical solution obtained by using CCW approximation method. Detailed studies are carried out for two different physically meaningful non-ideal medium in the presence of magnetic field. Also, the effect on magnetic field of flow variables such as density, velocity, pressure and magnetic pressure behind the wave front is illustrated through figures. © Springer Science+Business Media B.V. 2010.